2019
DOI: 10.5334/tohm.466
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Correlation of Non-motor Symptoms in Adult Patients with Idiopathic Focal or Segmental Dystonia

Abstract: Background: Idiopathic focal dystonia is a motor syndrome associated with dysfunction of basal ganglia circuits. Observations have suggested that many other non-motor symptoms may also be part of the clinical picture. The aim was to assess the prevalence and correlation of non-motor symptoms in patients with common idiopathic focal or segmental dystonia. Methods: In a single-center cross-sectional case-control study, we evaluated the presence of pain, neuropsychiatric symptoms, and sleep alterations in 28 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 36 publications
(47 reference statements)
3
37
0
2
Order By: Relevance
“…28 For comparison, patients with PD suffered from more severe apathy in both studies, 27,28 and apathy was linked with cognitive decline in PD. 22 A Brazilian study 29 Simultaneous screening for NMS by both approaches may increase the detection rate, however, at the cost of increased clinical effort.…”
Section: Ta B L E 5 Correlations Between the Domains Of Health-relatementioning
confidence: 99%
“…28 For comparison, patients with PD suffered from more severe apathy in both studies, 27,28 and apathy was linked with cognitive decline in PD. 22 A Brazilian study 29 Simultaneous screening for NMS by both approaches may increase the detection rate, however, at the cost of increased clinical effort.…”
Section: Ta B L E 5 Correlations Between the Domains Of Health-relatementioning
confidence: 99%
“…Many people living with dystonia experience non-motor symptoms contributing to disability and reducing participation in daily activities (Smit et al 2017a;Stamelou et al 2012; Torres and Rosales 2017), leading to the development of non-motor symptom scales for dystonia (Smit et al 2017a;Klingelhoefer et al 2019). Non-motor symptoms featured strongly when people with CD were asked about their most burdensome symptoms (Smit et al 2017a) and the most prevalent experienced by people with idiopathic, isolated dystonia were pain, depression, anxiety, apathy, and impaired sleep (Smit et al 2017a;Novaretti et al 2019). Other non-motor symptoms such as fatigue, catastrophizing, sensorimotor disturbances, olfactory and visual problems have also been noted amongst others, and also impact negatively on quality of life (Zetterberg et al 2009).…”
Section: Non-motor Symptomsmentioning
confidence: 99%
“…disorder (35,36), other neuropsychiatric manifestations have been highlighted as features of dystonia, particularly in the past decade (10)(11)(12)(13)(14)(15). Furthermore, emerging evidence suggests that dystonia results from dysfunctional brain networks (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…As the BG are connected to the limbic system, its dysfunction induces consequent non-motor neuropsychiatric symptoms in patients with dystonia (3)(4)(5). Indeed, recent studies have shown that such neuropsychiatric manifestations, including depression, anxiety, and obsessive-compulsive traits, are observed in patients with focal or segmental dystonia (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The recent finding that patients with essential tremor (ET), a common motor characterized dysfunction of the cerebellum and consequent isolated tremor, also present with neuropsychiatric symptoms, may implicate psychiatric manifestations as part of the primary pathophysiology of movement disorders (3,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%